The MOBIOS+: A FAIR (Findable, Accessible, Interoperable and Reusable) database for Mindanao's terrestrial biodiversity - Krizler Tanalgo; Kier Dela Cruz; Angelo Agduma; Jeaneth Magelen Respicio; Sumaira Abdullah; Renee Jane Alvaro-Ele; Bona Abigail Hilario-Husain; Meriam Manampan-Rubio; Sedra Murray; Lothy Casim; Athea Mohidda Pantog; Shiela Mae Balase; et al. (Biodiversity Data Journal, 2023)
Due to its complex geological history and the emergence of various biogeographic regions, the Philippines boasts an extraordinary array of flora and fauna. This unique combination has contributed to the country’s exceptional density of terrestrial species, making it amongst the highest in the world. Mindanao, in the southern part of the Philippines, is the second largest group of islands and supports high levels of endemism and proportion of threatened species. However, consolidated biodiversity records and information remain unavailable for the region. The primary goal of the Mindanao Open Biodiversity Information (MOBIOS+) database is to address these substantial data deficiencies by compiling contemporary biodiversity information from the 21st century. This initiative seeks to enhance our comprehension of biodiversity trends in Mindanao over temporal and spatial dimensions, while also creating an openly-accessible database. The database we present here is the first of its kind and currently the most comprehensive attempt to establish the largest consolidated database for Mindanao biodiversity, based on publicly available literature. With its vast collection of biodiversity data, this database will prove to be a valuable resource for advancing biodiversity research and analysis. It will further facilitate the identification of species and areas that require immediate conservation prioritisation and action, addressing the urgent challenges posed by our rapidly changing planet.The MOBIOS+ database is the first attempt to create a massive FAIR database aiming to collate biodiversity records from published literature in the Mindanao faunal region, south of the Philippines. The database currently includes 12,813 georeferenced specimen occurrences representing 1,907 unique taxa across 10 animal classes inhabiting the terrestrial and freshwater environments of Mindanao faunal region. We made all georeferenced specimen occurrences available in the Global Biodiversity Information Facility (GBIF) platform.